Developing, Piloting and Scaling-up of Nepal’s Neonatal Care Program - Poudel, D C; Acharya, B; Pant, S; Poudel, D; Pradhan, Y V (Journal of Nepal Health Research Council, 2012)
The Community-based Newborn Care Package  is  a  set of neonatal  care  interventions  to  be delivered  through  the existing  government  system  of  facility-based  health  workers  and  community  based  volunteers  in  Nepal.  The package was  developed  by  the  government  of Nepal  in  2007  based  on  the  evidence  from Nepal  and  neighboring countries  and  designed  to  be  implemented  as  a  comprehensive  package  to  improve  newborn  survival. This  paper reviews  the process, progress, and  lessons  learned  from  the program design, early-implementation and monitoring and  provides  future  directives  to  improve  upon  this  integrated  package  that  uses  a  continuum  of  care  approach from  the  pre-pregnancy  to  neonatal  periods  by  involving  the  communities,  health workers  and  the  private  sector. Keywords: Community-Based Neonatal Care Package; integrated package; Female Community Health Volunteer; neonatal mortality; Nepal.